Recommend or not : is generation the key? A perspective from the SOR paradigm for online stores in Colombia (2020)
Word-of-mouth behavior is one of the most effective marketing communications. Despite not being able to be controlled by the company, it can be influenced. Its importance lies in its effectiveness in repeat sales and attracting new customers. However, in the study of consumer behavior, it has been shown that the differences between subgroups can be relevant for the business sector, allowing it to generate specific strategies for each segment. In that respect, this research aims to find the determinants of WOM in generations X and Y to know the meanings these consumers give to the elements proposed within the SOR paradigm. A quantitative study was conducted using a sample of 537 e-commerce customers surveyed with a structured questionnaire to test the proposed relationships. Results are analyzed with structural equations, and a multigroup analysis is presented to find the differences between generation X and generation Y. The results indicate that, for millennials, the ease of use of electronic stores is essential to enjoying the shopping experience. Implications are discussed in the paper.